2017
DOI: 10.1111/ajad.12606
|View full text |Cite
|
Sign up to set email alerts
|

Religious coping in patients with severe substance use disorders receiving acute inpatient detoxification

Abstract: Background and Objectives Religious coping, one of the most widely studied components of spirituality among psychiatric populations, has rarely been addressed in patients with severe substance use disorders (SUD). The aim of our study was to elucidate whether religious coping is related to symptom expression and mutual-help participation. Methods Self-reported religious coping was assessed in individuals sequentially admitted to a private psychiatric hospital for inpatient detoxification. Target symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
2
23
0
3
Order By: Relevance
“…People who use PRC tend to seek spiritual support and meaning when inflicted by traumatic events; by contrast, people who resort to negative religious coping (NRC) can have a hard time recovering, as they experience spiritual complications and express doubt about the issues of God and faith. For instance, Medlock et al (2017) found that PRC had a positive correlation with a patient’s reduced cravings and increased productive participation in 12-step meetings, whereas patients who relied on NRC suffered withdrawal symptoms more acutely and benefited less from the 12-step meetings.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…People who use PRC tend to seek spiritual support and meaning when inflicted by traumatic events; by contrast, people who resort to negative religious coping (NRC) can have a hard time recovering, as they experience spiritual complications and express doubt about the issues of God and faith. For instance, Medlock et al (2017) found that PRC had a positive correlation with a patient’s reduced cravings and increased productive participation in 12-step meetings, whereas patients who relied on NRC suffered withdrawal symptoms more acutely and benefited less from the 12-step meetings.…”
Section: Sections Of the Studymentioning
confidence: 99%
“…In addition, factors such as addicted friends, psychological stress, referring to the former locations or hangouts, unpleasant situations, being rejected by the family and society, and seeing the tools and objects of drug use are other factors in this regard [14]. Studies have shown that religion and its related variables decrease suicidal behaviors [15] and drug use [16]. Unfortunately, numerous studies have shown that there is a high likelihood of relapse into substance use after stopping it.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that religion and its related variables lead to a decrease in suicidal behaviors (19). and drug abuse (20). Considering the positive relationship between the religious attitude and the quality of life of addicted people, it is believed that institutionalization of religious beliefs and the related practice can help these people gain self-esteem, self confidence and dignity.…”
Section: Discussionmentioning
confidence: 99%